KARAKTERISTIK PAPAN PARTIKEL LIMBAH KAYU MAHONI DAN SENGON DENGAN PERLAKUAN PENGAWETAN ASAP CAIR - , Agus Ngadianto ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Particleboard is a product that commonly used as substitution for solid wood. The weakness of this particleboard is vulnerable to wood destroying organisms, such as termites, due to it is from low-grade durability of wood raw materials. Therefore, it needs some precaution to get a good quality of particleboard which has a high durability properties against wood destroying organisms. The purpose of this research is to find out the effect of preservation treatment by liquid smoke and the amount of urea formaldehyde on particleboard properties made of mahogany and falcata wood wastes as well as to find out its resilience against dry wood termites Cryptotermes cynocephalus Light. The particleboard was made from mahogany and falcata wood wastes using urea formaldehyde adhesive by hot press system. This research using a preservation treatment with liquid smoke in the raw material at different concentrations (0%, 2.5%, and 5%) and the amount of adhesive of 7.5% and 15%. Physical and mechanical properties were tested according to standard JIS A 5908-1994 (type-8) which included : density, moisture content, water absorption, thickness swelling, internal bonding, modulus of rupture, and modulus of elasticity. Mortality of dry wood termites and weight loss of the samples were then calculated. The result showed that mahogany particleboard using 15% urea formaldehyde adhesive, preserved by 5% liquid smoke gave the best performance, i.e. physical and mechanical properties met JIS A 5908-1994 (type-8). However, falcata particleboard using 15% urea formaldehyde adhesive and preserved by 2.5% liquid smoke gave the best performances except in thickness swelling. The highest mortality value and the lowest weight loss were found at 5% liquid smoke and 15% urea formaldehyde adhesive, i.e. 90.67% and 0.408% for mahogany particleboard and 64.67% and 0.83% for falcata particleboard.